Liquid-mediated particle capture by nonwoven filter media for automotive engine intake air filtration. Issue 4 (June 2022) - Yadav, Shivendra; Das, Dipayan
This article reports on development, characterization, and performance of liquid-treated nonwoven air filter media for automotive engine intake application. A polypropylene fiber-based needle-punched nonwoven fabric was prepared for treatment with four viscous liquids (glycerol, SAE 20W/50 engine oil, PEG 400, and deionized water) by liquid spraying technique. The filtration performance was evaluated in terms of initial and final gravimetric filtration efficiencies, fractional filtration efficiency, evolution of pressure drop, and dust holding capacity. The liquid-treated filter media registered higher gravimetric as well as fractional filtration efficiency and higher dust holding capacity as compared to the untreated ones. The initial and final gravimetric filtration efficiencies were found to be directly related to liquid add-on via a power law relationship. The liquid-treated filter media also exhibited higher fractional filtration efficiency than their untreated counterparts for all sizes of tested particles. Interestingly, the increase of fractional efficiency was more for smaller particles as compared to larger ones. This was explained quantitatively through single fiber efficiency due to adhesion. The viscosity of liquid was found to be a very crucial parameter as the dust deposition morphology was contingent to the flow of liquid onto the filter media. The stickiest liquid yielded highest filtration efficiencies, displayed slowest rise of pressure drop, and exhibited highest dust holding capacity.